Predictors of Institutional Delivery in Nepal: Analyzing Nepal Demographic and Health Survey 2016 - Parajuli, Ashya; K.C., Janak; Magar, Esther Budha; Chaudhary, Ranjana; Gupta, Mala; Marahatta, Deepak (Journal of Multidisciplinary Research Advancements, 2023)
Nepal has made remarkable progress in reducing the MMR and achieving the MMR-related goal of MDG-5A by 2015. Still, a substantial number of women deliver at home. Still, a significant number of women deliver at home. WHO estimated that 15% of women will suffer severe complications during delivery and pregnancy, leading to most maternal deaths. In Nepal, 1 out of 2 neonatal deaths and 2 out of 5 maternal deaths occur at home. Due to this, institutional delivery is considered the key and proven intervention to reduce maternal and neonatal mortality. The study aims to assess the trends in institutional delivery and its associated factors in Nepal. This study used the Nepal Demographic and Health Survey 2016 dataset to analyze a subset of 5060 women aged 15–49 who had given birth within the five years before the survey. The survey employed a three-stage cluster sampling method for the urban region and a two-stage cluster sampling method for the rural region, including the most recent birth in the study. The obtained data were weighted and analyzed using Chi-square, and the variables found to be significant in Chi-square were introduced with bivariate and multivariate logistic regression to identify the predictors. This study found that caste/ethnicity, place of residence, ecological zone, province, wealth quintile, mother’s education, occupation, birth order, ANC visit, and birth preparedness were independently associated with institutional delivery. To achieve the SDG target of 90% by 2030, we must address these factors and increase the institutional delivery rate.